Big Rural: Rural Industrial Places, Democracy, and What Next - Marshall, Crystal Cook (Lexington Books, 2023)
In Big Rural: Rural Industrial Places, Democracy, and What Next, Crystal Cook Marshall unveils the rural not as wild and unknowable but as measured and intervened-in as big cities. Drawing international comparisons with a case study centering on the Pocahontas Coalfield, Cook Marshall documents that rural places are often systems among systems that scientists and engineers heavily shape both in landscape and culture. Often single sector economies with consolidated power and automation away of jobs, these rural industrial places compound the problems of their inhabitants, even threatening their capacity to practice democracy. Cook Marshall interacts with rural interveners from industry to Rural Studies and Science and Technology scholars to policy advocates, also detailing the gaps in related scholarship. Building from analysis, she proposes a range of antidotes to the extraction and destruction of “Big Rural” both in material life and in knowledge, such as potential National Rural and Sustainable Agricultural strategies. Through these, in interviews with rural change agents, through research, and through local and federal paths, Cook Marshall asserts a way forward for the rural that is more equitable and just.